Doctor, Doctor! I Can Walk! - van Helmond, Wiet (Homœopathic Links, 2013)
“Delusion he is walking on his knees.” We all know this as one of the keynote rubrics for Baryta. It beautifully illustrates the combined inner feelings of being smaller or underdeveloped and everybodyʼs able to see it. It is due to delusional concepts such as this that the patientʼs development is often severely stagnated. And although very well compensated he does not come to full bloom as a person until we give the much needed similimum.
Keywords: Baryta carbonica; Development arrested